2013
DOI: 10.1371/journal.pone.0075932
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Biochar Research, with a Focus on Its Stability in situ and Its Promise as a Climate Mitigation Strategy

Abstract: BackgroundClaims about the environmental benefits of charring biomass and applying the resulting “biochar” to soil are impressive. If true, they could influence land management worldwide. Alleged benefits include increased crop yields, soil fertility, and water-holding capacity; the most widely discussed idea is that applying biochar to soil will mitigate climate change. This claim rests on the assumption that biochar persists for hundreds or thousands of years, thus storing carbon that would otherwise decompo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
121
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(132 citation statements)
references
References 74 publications
2
121
0
3
Order By: Relevance
“…Assuming a conservative aerobic decomposition rate for peat in substrates of 5% per annum (Cleary et al, 2005), within one century of mining and use in soil-free substrates 95% of mined peat would be expected to revert from a C sink to source (CO 2 ). In contrast, high-temperature BCs are thought to generally exhibit lower decomposition rates than undecomposed or humified biomass such as compost and peat (Woolf et al, 2010) and exhibit centennial to millennial residence times (Gurwick et al, 2013). The molar O:C = 0.36 for the BC in this study corresponds to a half-life of 100-1000 years (Spokas, 2010), suggesting that one century after production and use in soil-free substrates, at least 50% of C in the softwood BC in this study would be converted to CO 2 .…”
Section: Additional Advantages and Possibilities Of Bc Substitution Fmentioning
confidence: 99%
“…Assuming a conservative aerobic decomposition rate for peat in substrates of 5% per annum (Cleary et al, 2005), within one century of mining and use in soil-free substrates 95% of mined peat would be expected to revert from a C sink to source (CO 2 ). In contrast, high-temperature BCs are thought to generally exhibit lower decomposition rates than undecomposed or humified biomass such as compost and peat (Woolf et al, 2010) and exhibit centennial to millennial residence times (Gurwick et al, 2013). The molar O:C = 0.36 for the BC in this study corresponds to a half-life of 100-1000 years (Spokas, 2010), suggesting that one century after production and use in soil-free substrates, at least 50% of C in the softwood BC in this study would be converted to CO 2 .…”
Section: Additional Advantages and Possibilities Of Bc Substitution Fmentioning
confidence: 99%
“…In spite of the fact that the consequences of adding biochar to soils are still not fully understood (Spokas et al 2012;Gurwick et al 2013), this soil amender is expected to improve the productivity and environmental quality of agroecosystems similar to Amazonian Dark Earths (Novotny et al 2009). Research has demonstrated that biochars play a significant role in mitigating soil greenhouse gas emissions (Case et al 2012;Zhang et al 2013;Nelissen et al 2014), while others studies show the opposite (Troy et al 2013) or neutral effects (Mukome and Parik 2013;Suddick and Six 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale application of biochar in agriculture has been proposed as a promising technology for long-term C-sequestration and underground storage [104,105]. At the same time, much research and many (though not all) experimental applications of charcoal have demonstrated positive effects of black carbon on soil physical properties, including pore space; bulk density; water retention and infiltration [102,106,107]; soil chemical characteristics, such as a long-term increase in the cation exchange capacity [108,109], nutrient retention [110], improved P availability [111,112] (but frequently reduced N-availability [113], and reduced methane and nitrous oxide emissions [114][115][116] (but see [117,118]). Biochar applications have also been reported beneficial for soil biology, such as increases in mycorrhizal fungi [119] and in biological N 2 -fixation [120] (but see [121] and increases in overall diversity of the microbiota [103,122,123], despite the possible toxic nature of some biochar compounds [124].…”
Section: Biochar and Indian Blacksoilsmentioning
confidence: 99%